On the use of liposomal delivery systems for oxaliplatin and in dual drug delivery in combination with chemo-sensitizing and chemotherapeutic agents - Ibrahim, Ayat Zein-elabedeen Mohamed (AUC Knowledge Fountain, 2016)
Cancer is one of the rapidly growing leading causes of death worldwide where combinational chemotherapy is the most used strategy to control it. Drug delivery constitutes a major segment in chemotherapeutics including liposomes as a drug delivery system enabling the encapsulation of both hydrophilic and hydrophobic drugs. Recently, liposomes have been recognized as an efficient means for drug delivery of combinational chemotherapy. The aims of this study were to prepare stable liposomal formulations with particle sizes of less than 200 nm and that offer high encapsulation efficiency for oxaliplatin. Subsequently, the use of the developed liposomal system in dual drug loading was investigated using two approaches, oxaliplatin and a chemo-sensitizing agent, and oxaliplatin combined with a chemotherapeutic agent. In addition, the effect of dual drug loading on liposome characterization, in-vitro release profile and cytotoxic efficiency were investigated. In this study, all prepared liposomal formulations were highly stable upon long term storage. The dual chemotherapeutic loaded liposomal formulation demonstrated a significantly enhanced in-vitro cytotoxic efficiency, and DNA damage induction.